Mengintegrasikan Nilai-nilai Pancasila dalam Pendidikan untuk Membentuk Pemimpin Masa Depan - Rachmadanti, Nabila; Anggara, Restu; Lestari, Salwa Aulia; Khairani, Yaumil; Taun, Taun (TSAQOFAH, 2024)
The aim of this research is to find out how future leaders can apply Pancasila values in education, which include: 1. Belief in the One and Only God; 2. Just and civilized humanity; 3. The unity of Indonesia; 4. Democracy guided by the inner wisdom in the unanimity arising out of deliberations among representatives; and 5. Social justice for all Indonesian people. Character education is an effort to realize the values of Pancasila and the preamble of the 1945 Constitution. However, the evolving conditions in educational institutions today hinder character education. Therefore, it is crucial to embed Pancasila principles in future leaders to ensure they uphold and promote these fundamental values, fostering a strong national identity and moral integrity.